Opportunities and Challenges of Islamic Education Management in Facing the Global Era - Setyowati, Ratna Dewi; Ningsih, Dewi; Pahrudin, Agus (Graduate Program Magister Manajemen Pendidikan, 2024)
This research discusses the concept of a constructive paradigm in Islamic education management, with a focus on opportunities and challenges in the global era. It emphasizes the importance of innovation, developing teaching quality, and effective management in facing global dynamics. The aim of this research is to identify and analyze the implications of globalization for Islamic education. The research method uses a qualitative approach and a literature review to explore the impact of globalization on Islamic educational institutions. The research results show that there are positive opportunities, such as technological advances, as a basis for positive change, but also identify social and cultural challenges that require a holistic approach. Therefore, it can be concluded that this research emphasizes the need to develop quality and globally relevant Islamic educational institutions. In facing global challenges, there is a need to focus on innovation, improving the quality of teaching, and effective management to ensure the sustainability of Islamic education that makes a positive contribution to the global scope.